Non-occupational and occupational factors associated with specific SARS-CoV-2 antibodies among hospital workers – A multicentre cross-sectional study. (September 2021) - Kahlert, Christian R.; Persi, Raphael; Güsewell, Sabine; Egger, Thomas; Leal-Neto, Onicio B.; Sumer, Johannes; Flury, Domenica; Brucher, Angela; Lemmenmeier, Eva; Möller, J. Carsten; Rieder, Philip; Stocker, Reto; et al.
Abstract: Objectives: Protecting healthcare workers (HCWs) from coronavirus disease-19 (COVID-19) is critical to preserve the functioning of healthcare systems. We therefore assessed seroprevalence and identified risk factors for severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) seropositivity in this population. Methods: Between 22 June 22 and 15 August 2020, HCWs from institutions in northern/eastern Switzerland were screened for SARS-CoV-2 antibodies. We recorded baseline characteristics, non-occupational and occupational risk factors. We used pairwise tests of associations and multivariable logistic regression to identify factors associated with seropositivity. Results: Among 4664 HCWs from 23 healthcare facilities, 139 (3%) were seropositive. Non-occupational exposures independently associated with seropositivity were contact with a COVID-19-positive household (adjusted OR 59, 95% CI 33–106), stay in a COVID-19 hotspot (aOR 2.3, 95% CI 1.2–4.2) and male sex (aOR 1.9, 95% CI 1.1–3.1). Blood group 0 vs. non-0 (aOR 0.5, 95% CI 0.3–0.8), active smoking (aOR 0.4, 95% CI 0.2–0.7), living with children <12 years (aOR 0.3, 95% CI 0.2–0.6) and being a physician (aOR 0.2, 95% CI 0.1–0.5) were associated with decreased risk. Other occupational risk factors were close contact to COVID-19 patients (aOR 2.7, 95% CI 1.4–5.4), exposure to COVID-19-positive co-workers (aOR 1.9, 95% CI 1.1–2.9), poor knowledge of standard hygiene precautions (aOR 1.9, 95% CI 1.2–2.9) and frequent visits to the hospital canteen (aOR 2.3, 95% CI 1.4–3.8). Discussion: Living with COVID-19-positive households showed the strongest association with SARS-CoV-2 seropositivity. We identified several potentially modifiable work-related risk factors, which might allow mitigation of the COVID-19 risk among HCWs. The lower risk among those living with children, even after correction for multiple confounders, is remarkable and merits further study.